Relationship of Online Learning Methods with Time Management of During The WFH Due to Covid 19 Pandemic in North Sumatera - Pomarida Simbolon; Nagoklan Simbolon (Institute of Computer Science (IOCS), 2020)
Time management is a self-regulatory individual in using time as effectively and as possible which is influenced by several factors such as self regulation, motivation, and learning methods. The purpose of this research is to know the relationship of online learning methods with the management of duration of student study time during WFH due to pandemic Covid19 in North Sumatra province. This type of research is correlational design with Cross sectional research design. The population in the research of all students in North Sumatra province with a sample number of 96 people. Sampling techniques using accidental sampling. Data collection using a questionnaire sheet. Analyze data using Chi Square test. The results of the study gained an online learning method of both 82 people (85.4%), a time management study of both 70 people (72.9%). Chi Square test results obtained p-value = 0.006 (P< 0.05). This indicates there is an online learning method relationship with the management of duration of student study time during WFH due to pandemic Covid19 in North Sumatra province. It is hoped that students can perform better online learning in order to better improve their self-discipline in managing their time, especially in the duration of time management for good learning.